(untitled) (Semiárida, 2020)
The estimation of the percentages of slowly and non-digestible tissues allows the prediction 01the nutritive value of forages. In this study, the percentages of tissues in sheaths and blades of two species natives of the Salado Basin and abundant in the Pampas range pastures (Elytrigia scabrifolia y E. scabriglumis) were determined as a primary evaluation of their forage qualily. The estimations were done in the vegetative and reproductive stages. A split-plots design in space and time, with species as main plot, plant part (sheath or blade) as secondary plots, and three replications was used. Percentages of all leaf tissues were estimated by microscopic analysis of cross section and were grouped in rapidly and slowly plus non-digestible tissues. The variation of all leaf tissues between species, plant parts and growth stage, and the percentages variation of slowly and non-digestible tissues were analysed by principal components and by ANOVA, respectively. In all cases, the percentages of sclerenchyma were lower than 10% and those of slowly plus non-digestible tissues were lower than 45%. The percentages of slowly and non-digestible tissues did not differ (P<0.05) either between species (P<0.05) or plant parts, but increased 34% with the advancement of growth from the vegetativa to the reproductive stage. Although the percentage of slowly and nondigestible tissues suggest that both species have an acceptable nutritive value, this rating could be altered by the degree of forage lignification. Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Publicado en Archivos latinoamericanos de producción animal, 5(Supl. 1): 118-121, 1997.